Shedding Light on Shadow Banking - Harutyunyan, Artak (IMF Working Papers; Working Paper ;, 2015)
In this paper, we develop an alternative approach to estimate the size of the shadow banking system, using official data reported to the IMF complemented by other data sources. We base our alternative approach on the expansion of the noncore liabilities concept developed in recent literature to encompass all noncore liabilities of both bank and nonbank financial institutions. As opposed to existing measures of shadow banking, our newly developed measures capture nontraditional funding raised by traditional banks. We apply the new approach to 26 jurisdictions and analyze the results over a twelve-year span. We find that noncore liabilities are procyclical and display more volatility than core liabilities for most jurisdictions in the sample. We also compare our measures to existing measures, such as the measure developed by the Financial Stability Board. Our approach can be replicated over time using internationally-comparable data and thus may serve as an operational tool for IMF surveillance and policy analysis.